Critical Evaluation of Possible Contamination by Toxic Metals in Powdered Milk During the Production Process (JOURNAL OF ADVANCES IN CHEMISTRY, 2012)
This study used an interdisciplinary approach to bring together some of the necessary and fundamental knowledge in the processing of powdered milk, mainly in relation to the materials used in the manufacture of equipment used in industrial processing. In order to clarify this issue, questions are presented on problems of corrosion, erosion and contamination by microorganisms that can generate or contribute to toxic metal leaching and consequently contaminate milk powder. In this work, we developed a method using atomic absorption spectroscopy with electro-thermal atomization to determine levels of cadmium, lead and nickel. To evaluate the possibility of contamination, we tested 15 samples of various brands of milk powder purchased in shops. Fortunately, the levels of these elements, in all samples, were lower than the maxima allowed under Brazilian law. However, this method of chemical analysis can be used as a tool of quality as the contamination that may occur during the production process.